PENERAPAN FISIOTERAPI DADA UNTUK MENIGKATKAN BERSIHAN JALAN NAFAS PADA ANAK DENGAN PNEUMONIA DI RSUP Dr. SARDJITO - Subekti, Lufia Anggraini; Purnamaningsih, Sumarti Endah; Ambarwati, Ambarwati (Jurnal Kesehatan Karya Husada, 2023)
Background: Pneumonia is an infection of the respiratory tract that causes the air sacs of the lungs to fill with pus or fluid which causes difficulty breathing, obtained data as many as 808,694 children died from pneumonia. One of the treatments for pneumonia is chest physiotherapy. Objective: To determine the implementation of chest physiotherapy to improve airway clearance in paediatric patients with pneumonia at Dr Sardjito Hospital Yogyakarta. Methods: Collecting complete data information by direct observation, recording, and reporting the results obtained. Chest physiotherapy was performed twice a day for 6 days from 13-18 March 2023. Results: This chest physiotherapy was given twice a day in the morning and evening for 6 days, during the chest physiotherapy action there were many changes in children such as breathing patterns, breathing frequency, children can spit out phlegm, not shortness of breath. Conclusion: Based on the study, it can be concluded that chest physiotherapy can be effective in helping airway clearance in children with pneumonia who have airway disorders. Keywords: Chest Physiotherapy, Airway Clearance, Pneumonia